(untitled) (Texas Journal of Agriculture and Biological Sciences, 2022)
This study was conducted to evaluate the nutritive value of sweet potato peels. The proximate composition, mineral composition, amino acid profile and anti-nutritional factors were determined in airdried and sun-dried sweet potato peels. The sweet potato peels used for this research was collected from Gwagwalada and its environs. The results of the analysis show that crude protein (7.89%, 5.63%), crude fibre (3.41%, 3.68%), ether extract (1.71%, 2.15%), ash (6.95%, 5.82%), moisture (10.00%, 11.50%) and nitrogen free extract (70.04%, 71.22%) for air-dried and sun-dried sweet potato peels respectively. The airdried and sun-dried peels had the following macro mineral contents respectively: calcium (61.70mg/100g, 45.73mg/100g), magnesium (9.33mg/100g, 5.11mg/100g), potassium (10.3mg/100g, 10.74mg/100g), sodium (4.12mg/100g, 1.52mg/100g), phosphorus (21.81mg/100g, 20.45mg/100g). The micro mineral content of zinc (1.00mg/100g) and iron (3.14mg/100g) in air-dried sweet potato peels had a higher value than that of sun-dried sweet potato peels. Sun-dried sweet potato peels had a higher value in copper (1.33mg/100g) and cobalt (0.18mg/100g) compared to the air-dried sweet potato peels. The air-dried and sun-dried sweet potato peels have the same manganese (1.22mg/100g) deposit in the mineral contents. A total of 16 amino acids (lysine, arginine, aspartic acid, threonine, histidine, serine, glycine, alanine, cystine, valine, leucine, phenylalanine, Tryosine, isoleucine, proline and methionine) were identified in the air-dried and sun-dried sweet potato peels, 9 of which were essential amino acid (lysine, arginine, threonine, histidine, valine, leucine, phenylalanine, isoleucine and methionine).